Navigating The Global And Local: The Intersection Of Religious Symbolism In Indonesian Literature And Islamic Modernization - Mahbubi, M; Ahmad, Amala Bilqis (Titian: Jurnal Ilmu Humaniora, 2025)
This study examines the influence of globalization on religious symbolism in Indonesian literature, focusing on the role of religious symbols in literature that reflects local religious identity and responses to Islamic modernization. The research aims to understand how Indonesian writers interpret Islamic symbolism in the face of global influences and how these symbols remain relevant in shaping religious identity in Indonesia. A qualitative approach with content analysis was used on literary works depicting religious symbols. The results show that despite the strong global influence, local religious symbolism still plays a central role in defining Indonesian religious identity, with writers adapting these symbols to reflect broader social dynamics. This study contributes to the understanding of how Indonesian literature responds to globalization and introduces relevant religious values in a contemporary context. Abstrak Penelitian ini mengkaji pengaruh globalisasi terhadap simbolisme agama dalam sastra Indonesia, dengan fokus pada peran simbol agama dalam literatur yang mencerminkan identitas agama lokal dan respon terhadap pengaruh modernisasi Islam. Penelitian ini bertujuan untuk memahami bagaimana penulis Indonesia menginterpretasikan simbolisme Islam di tengah pengaruh global, serta bagaimana simbol tersebut tetap relevan dalam membentuk identitas agama di Indonesia. Metode yang digunakan adalah pendekatan kualitatif dengan analisis konten pada karya sastra yang menggambarkan simbol-simbol agama. Hasil penelitian menunjukkan bahwa meskipun terdapat pengaruh global yang kuat, simbolisme agama lokal tetap memainkan peran sentral dalam mendefinisikan identitas agama Indonesia, dengan penulis yang menyesuaikan simbol tersebut untuk mencerminkan dinamika sosial yang lebih luas. Penelitian ini berkontribusi pada pemahaman bagaimana sastra Indonesia menanggapi globalisasi dan memperkenalkan nilai-nilai agama yang relevan dalam konteks kontemporer.